Evaluation and inter-comparison of satellite precipitation estimations for extreme flood events in Peninsular Malaysia / Eugene Soo Zhen Xiang - Eugene Soo , Zhen Xiang (2020)
Satellite precipitation products (SPP) have been useful in any hydrological applications as their extensive spatial coverage and finer space and time resolutions. However, these satellite estimations exhibit large systematic and random errors which may cause large uncertainties in any hydrological applications. In this study, three advanced satellite precipitation products, i.e. CMORPH, TRMM 3B42V7, and PERSIANN are utilized in conjunction with the ground observation to investigate their performance in detecting rain, capturing storms and rainfall pattern during extreme flood events. This study evaluates and compares the capability of the SPP by focusing on the 2014-2015 northeast monsoon extreme flood events. Three affected river basins, i.e. Kelantan (13,100 km2), Johor (1,652 km2) and Langat river basin (2,350 km2) are chosen as study areas. Firstly, to compare with the grid-based satellite estimations, a validation between five spatial interpolation methods (Arithmetic Mean (AM), Thiessen Polygon (TP), Inverse Distance Weighting (IDW), Ordinary Kriging (OK), and Spline (SP)) with ground observations is done whereby the result shows that none of the spatial interpolation methods is superior to the others. Furthermore, the result shows that all three SPP have performed reasonably well for the Kelantan river basin whereas for the other two river basins, only TRMM and CMORPH perform better. As these SPP exhibit biases, the three widely used approaches of bias correction, namely Linear Scaling (LS), Local Intensity Scaling (LOCI) and Power Transformation (PT) are applied on the daily SPP to improve the estimations. Bias correction analysis is performed using the aforementioned methods to the Langat river basin only. Findings indicate that the LS scheme is able to match the mean precipitation of every SPP but does not correct the standard deviation (SD) and coefficient of variation (CV) of the estimations regardless of extreme floods selected. For the LOCI scheme, TRMM and CMORPH estimations in certain floods show a significant improvement in the result but not for PERSIANN. PT scheme is found to be the best method as it improves most of the statistical performances as well as the rainfall distribution of the floods. In addition, this study also evaluates the sensitivity of the parameters used in the BC process where the result indicates that the PT scheme is found to be the least sensitive in correcting the daily SPP compared to the other two schemes. Finally, this study performs rainfallrunoff simulation by employing the Hydrological Modelling System (HEC-HMS) to validate the performance of the raw and bias-adjusted SPP for the 2014-2015 flood events in the Langat river basin. Generally, corrected precipitations exhibit a significant improvement during the high rainfall event especially LOCI-adjusted TRMM and CMORPH. For PERSIANN-simulated flow, the BC schemes are able to improve the discharge simulation. However, further calibration is suggested in order to enhance its accuracy.